Trastuzumab for the Treatment of Salivary Duct Carcinoma - Limaye, Sewanti A. (AlphaMed Press, 2013)
OBJECTIVES. Salivary duct carcinoma (SDC) is a rare and aggressive malignancy with high mortality and poor response to treatment. A significant fraction of SDCs are HER2 positive. This retrospective review examines HER2 testing in SDC and the outcome of trastuzumab-based therapy in adjuvant and palliative settings. METHODS. A total of 13 patients with SDC and HER2/neu expression by immunohistochemistry of 1–3+ were treated with trastuzumab in adjuvant (n = 8) or palliative (n = 5) setting. Adjuvant therapy consisted of concurrent radiation and chemotherapy with weekly paclitaxel, carboplatin, and trastuzumab (TCH) for 6 weeks followed by TCH for 12 weeks and trastuzumab alone for 1 year. Palliative treatment for metastatic disease consisted of TCH every 3 weeks for 6 cycles followed by trastuzumab for variable time periods with or without second-line chemotherapy for progression. All patients had fluorescence in situ hybridization testing for HER2/neu gene amplification. RESULTS. The median duration of follow-up was 27 months (range: 8–48 months). In all, 62% of adjuvant patients (5/8) had no evidence of disease more than 2 years from completion of therapy. All patients with metastatic disease (5/5 patients) responded to treatment with TCH. One patient achieved a complete response and remains with no evidence of disease 52 months after initiation of TCH. The median duration of response was 18 months (range: 8–52 months). CONCLUSION. HER2/neu positivity and treatment with trastuzumab correlated well with long-term survival and response in our patients. Based on this data, we propose that HER2/neu status be examined routinely in all patients with SDCs and the treatment be directed accordingly.